Acute laryngitis and croup: diagnosis and treatment - Murtaza Mustafa; P. Patawari; Rajesh Kumar Muniandy; MM. Sien; M. Tanveer Hossain Parash; J. Sieman (IOSR Journal, 2015)
Croup is a common respiratory tract infection, among children between 6 months and 5-6 years. Croup is characterized by “barking cough”, resembling the call of a seal or sea lion. The stridor is worsened by agitation or crying, and it can be heard at rest, it may indicate critical narrowing of the airways.The virus initially infects the upper respiratory tract and usually produce congestion of the nasal passages and nasopharynx, subsequently, the larynx, the trachea and bronchi are involved. The classic croup- stridor, hoarseness, and cough-arise mostly from the inflammation of larynx and trachea.Parainfluenza virus type 1 is the most frequent cause of croup,with adenoviruses, enteroviruses and Mycoplasma pneumonia.Diagnosis is on clinical manifestations, and the history especially for the younger children.Roentgenographic evaluation is unnecessary, the radiologic picture may be helpful in differential diagnosis. Guidelines for management of croup have been classified as mild,moderate and severe, Westley score of 0 to 2 mild cases, moderately severe score 3 to 7,severe cases with a score of 8 to 11,and high risk score of12 to 17 with imminent respiratory failure.Dexamethosone and budesonide are effective, nebulized epinephrineracemic epinephrine or1- epinephrine may be added to the dexamethasone for severe croup.